1993
DOI: 10.1364/ao.32.001839
|View full text |Cite
|
Sign up to set email alerts
|

Digital speckle-displacement measurement using a complex spectrum method

Abstract: An alternative approach to fully automatic speckle-displacement measurement is described. Two speckle patterns of a specimen, one before and one after deformation, are captured by a CCD camera and registered by a frame grabber. Two series of small subimages are obtained by segmenting the two speckle patterns. The corresponding subimage pairs extracted from both series are analyzed pointwise. The interrogation of each subimage pair involves a two-step fast-Fourier transform. While the first-step fast-Fourier tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
129
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(131 citation statements)
references
References 18 publications
0
129
0
2
Order By: Relevance
“…The simplest image-matching procedure is cross-correlation, which can be performed either in the physical space [14,15] or in Fourier space [16][17][18].…”
Section: Sandwiched-beam Technique For Precrackingmentioning
confidence: 99%
“…The simplest image-matching procedure is cross-correlation, which can be performed either in the physical space [14,15] or in Fourier space [16][17][18].…”
Section: Sandwiched-beam Technique For Precrackingmentioning
confidence: 99%
“…In 1993, Chen et al [27] suggested that the full-field displacements, u and v, of a specimen could be determined using a two-step Fast-Fourier Transform (FFT) algorithm. In the first step, the complex spectra of selected subsets from the reference and the deformed images were calculated and the resultant spectrum was then determined based on the phase difference of the two spectra.…”
Section: Improvement Of 2d-dic Algorithms Regarding Their Computationmentioning
confidence: 99%
“…The sharpest peak location of the normalized cross-correlation presents the pipette tip position. A bi-parabolic interpolation of the cross-correlation peak could be performed [15], for sub-pixel detection if needed.…”
Section: Pipettes Trackingmentioning
confidence: 99%